INFLUENCE OF ISLAMIC PERSPECTIVES ON ITSBAT MARRIAGE PETITION IN RELIGION COURT OF METRO CITY - Intan Pelangi; Ariza Umami (Universitas Muhammadiyah Metro, 2017)
Marriage is a bond between a man and a woman committed to becoming a family. Marriage is a legal social form that describes the smallest social accountability and its legal certainty. Register marriage is a form of welfare in Islamic law family. Islamic Compilations Law (KHI) also regulates itsbat marriage or the institution of marriage that is done by competent authorities on her marriage was not recorded.The aim of this research was to determine the influence of Islamic perspective in an itsbat marriage petition at the Religious Court in Metro city as one of the agencies, legal guarantee to the community of Moslems. The author conducted the research used empiric jurisdictional approach. The analytical method used was descriptive qualitative data. The result of this research is Islam perception becomes the most important thing to regulates itsbat marriage with the divorce as the main factors.